2021
DOI: 10.21468/scipostphyscore.4.2.008
|View full text |Cite
|
Sign up to set email alerts
|

Mean-field model of interacting quasilocalized excitations in glasses

Abstract: Structural glasses feature quasilocalized excitations whose frequencies \omegaω follow a universal density of states {D}(\omega)\!\sim\!\omega^4D(ω)∼ω4. Yet, the underlying physics behind this universality is not fully understood. Here we study a mean-field model of quasilocalized excitations in glasses, viewed as groups of particles embedded inside an elastic medium and described collectively as anharmonic oscillators. The oscillators, whose harmonic stiffness is taken from a rather featureless probability di… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 41 publications
6
29
0
Order By: Relevance
“…The model and its phase diagram -We consider the KHGPS model recently introduced in [29,30]. This model is an evolution of a model introduced by Gurevich Parshin and Schöber [31] and whose mean field limit has been considered by Kühn and Hortsmann in [32].…”
Section: Introduction -mentioning
confidence: 99%
“…The model and its phase diagram -We consider the KHGPS model recently introduced in [29,30]. This model is an evolution of a model introduced by Gurevich Parshin and Schöber [31] and whose mean field limit has been considered by Kühn and Hortsmann in [32].…”
Section: Introduction -mentioning
confidence: 99%
“…In [60] it has been shown that at small external field the density of states is purely quadratic D(ω) ∼ ω 2 as correctly predicted by mean-field models, and the corresponding modes are delocalized. On the other hand, upon increasing the external field, a quartic pseudogap D(ω) ∼ ω 4 takes place associated with the appearance of localized modes.…”
Section: G Connections With a Disordered Instance Of A Two-level System (Tls)mentioning
confidence: 61%
“…In a recent paper [60], a generalization of the Kühn and Horstmann (KH) model combined with the Gurevich, Parshin and Schober (GPS) three-dimensional lattice version in the presence of random interactions and a constant external field has been proposed in order to study zerotemperature vibrational modes of a specifically designed disordered system. The model is formulated as a collection of anharmonic oscillators subject to a random distribution p(κ) for the stiffnesses κ, which are taken uniform in the interval [κ min , κ max ] for positive or zero values.…”
Section: G Connections With a Disordered Instance Of A Two-level System (Tls)mentioning
confidence: 99%
“…The internal free-energies of TAP states and their Complexity are obtained by eqs. (17) and they read…”
Section: Appendix A: Computation Of the Monassonmentioning
confidence: 99%
“…It appears that deeper states in the landscape, corresponding to better optimized glasses, have less and less the low energy excitations, reflecting in smaller and smaller values of A 4 , and correspondingly, the excitations are more and more localized [12,13]. This spectrum of localized modes was first rationalized through phenomenological theories [14,15], while new predictions have recently enriched the picture [11][12][13][16][17][18][19]. In addition to typical ungapped minima, found by usual minimization protocols, it has been noticed in [20] that in some model glasses gapped mimima can be found through the use of smart minimization protocols that include particle swap [21,22].…”
Section: Introductionmentioning
confidence: 99%